EFFECTS OF IN SITU REMEDIATION ON THE SPECIATION AND BIOAVAILABILITY OF ZINC IN A SMELTER CONTAMINATED SOIL - Nachtegaal M.; Marcus M.A.; Sonke J.E.; Vangronsveld J.; Livi K.J.T.; van Der Lelie D.; Sparks D.L. (My University, 2005)
We report results from an extensive study on the speciation of zinc (Zn) and its relation to the mobility and bioavailablity of this element in a smelter contaminated soil and an in situ remediated area of this soil 12 yr after the application of cyclonic ash and compost. Emphasis was placed on the role of neoformed precipitates in controlling Zn speciation, mobility and bioavailability under different environmental conditions. Twelve years after remediation, the pH of the treated and non-treated soil differed by only 0.5 pH unit. Using state-of-the-art electron and X-ray microscopies in combination with micro-focused extended X-ray absorption fine structure (μ-EXAFS) spectroscopy, no major differences in Zn speciation were found between samples of the treated and non-treated soil. In both soils, 30% to 50% of Zn was present in smelter related minerals (willemite, hemimorphite or gahnite), while 50% to 70% of Zn was incorporated into newly formed Zn precipitates. Contrary to the non-treated soil, the treated soil did not contain gahnite or sphalerite; it is possible that these minerals were dissolved under the higher pH conditions at the time of treatment. Desorption experiments, using a stirred flow technique with a 0.1 mol/L CaCl2 (pH 6.5) and a HNO3 (pH 4.0) solution were employed to determine the exchangeable Zn fraction and the Zn fraction which will be mobilized under more extreme weathering conditions, respectively. No significant differences were found in desorption behavior between the treated vs. non-treated soil. Bioavailability tests, using the R. metallidurans AE1433 biosensor showed that ∼8% of total Zn was bioavailable in both the treated and non-treated soils. It was concluded that the incorporation of Zn into newly formed precipitates in both the treated and non treated soils leads to a significant natural attenuation of the exchangeable/bioavailable Zn fraction at near neutral pH conditions. At lower pHs, conditions not favorable to the formation of Zn precipitates, the pool of Zn associated with the secondary Zn precipitates is potentially more bioavailable.